NILAI BUDAYA KOMUNITAS BISSU DALAM NOVEL CALABAI, PEREMPUAN DALAM TUBUH LELAKI KARYA PEPI AL-BAYQUNIE - Aulia, Aulia; Nadeak, Parlindungan; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe cultural values of the Bissu community in novel Calabai, Perempuan dalam Tubuh Lelaki by Pepi Al-Bayqunie. This research can be useful for enriching the development of science and language studies and to be used as teaching materials for Indonesian language?s teacher. The method in this research is descriptive method with qualitative research. The approach in this research is literature anthropology approach. The source of data in this research is novel Calabai, Perempuan dalam Tubuh Lelaki by Pepi Al-Bayqunie published by Javanica. The primary data of this research reflected through the quotation of words, phrases, clauses, or sentences in the novel Calabai, Perempuan dalam Tubuh Lelaki. The technique of data collecting is using documentary study. The result of the research are: 1) cultural values from relationship between human and God, 2) relationship between human and nature, and relationship between human and another human. Keywords: Cultural values, Bissu community, Novel